1989
DOI: 10.1051/rnd:19890610
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of milk protein antigens across the intestinal epithelium in vitro

Abstract: Summary ― Degradations by proteolytic enzymes and intestinal epithelial permeability represent two major drawbacks to the transfer of food protein antigens to blood. These steps were studied in vitro for the milk protein antigens p-Lactogtobutin (!-Lg), a-Lactalbumin (a-La) and p-casein (!-cas). Pepsin-trypsin hydrolysis and permeability in isolated rabbit ileum in Ussing chamber were suited by ELISA and radiolabelled-protein measurement. Pepsin-trypsin hydrolysis showed an increasing resistance in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…antibodies and also several growth factors [1], In the bovine species, insulin-like growth factor I (IGF-I) is present in relatively high concentrations (400-600 pg/1) in the First colostrum [2][3][4], Receptors for IGF-I and IGF-I I are localized in the small intestine of neonatal calves [5]. Orally administered hu man recombinant IGF-I (rhIGF-I) exerts bio logical effects on the small gut and on meta bolic hormones in newborn calves [5][6][7], Var ious proteins and peptides can be absorbed in the small intestine by neonatal calves [8][9][10], but there is basically also evidence for se lective absorption of milk protein compo nents [11], Absorption of IGF-I was suspected to occur in the newborn calf [6], as in the neo natal piglet [ 12] and as has been shown in neo natal rats and lambs for epidermal growth fac tor [13,14], Thus, after colostrum intake, the IGF-I concentration in plasma in the new born calf slightly increased or the IGF-I con centration after birth remained elevated for a considerably longer time than in calves fed only water, glucose, milk or milk replacers on day 1 of life [2,[15][16][17], although effects of colostrum intake on IGF-I levels may not always be significant [ 18], In addition, follow ing oral administration of 1.1 and 6.2 mg of rhIGF-I to calves, IGF-I became elevated in blood plasma within hours in a dose-depen dent manner [1]. Furthermore, in calves IGF-I increased in blood plasma after the fourth day and remained elevated until day 20 of life [19], However, under these experimental con ditions, the rise of IGF-I could have been not only the consequence of enhanced absorption but also of an increased endogenous produc tion or of a decreased metabolic clearance rate.…”
Section: Introductionmentioning
confidence: 99%
“…antibodies and also several growth factors [1], In the bovine species, insulin-like growth factor I (IGF-I) is present in relatively high concentrations (400-600 pg/1) in the First colostrum [2][3][4], Receptors for IGF-I and IGF-I I are localized in the small intestine of neonatal calves [5]. Orally administered hu man recombinant IGF-I (rhIGF-I) exerts bio logical effects on the small gut and on meta bolic hormones in newborn calves [5][6][7], Var ious proteins and peptides can be absorbed in the small intestine by neonatal calves [8][9][10], but there is basically also evidence for se lective absorption of milk protein compo nents [11], Absorption of IGF-I was suspected to occur in the newborn calf [6], as in the neo natal piglet [ 12] and as has been shown in neo natal rats and lambs for epidermal growth fac tor [13,14], Thus, after colostrum intake, the IGF-I concentration in plasma in the new born calf slightly increased or the IGF-I con centration after birth remained elevated for a considerably longer time than in calves fed only water, glucose, milk or milk replacers on day 1 of life [2,[15][16][17], although effects of colostrum intake on IGF-I levels may not always be significant [ 18], In addition, follow ing oral administration of 1.1 and 6.2 mg of rhIGF-I to calves, IGF-I became elevated in blood plasma within hours in a dose-depen dent manner [1]. Furthermore, in calves IGF-I increased in blood plasma after the fourth day and remained elevated until day 20 of life [19], However, under these experimental con ditions, the rise of IGF-I could have been not only the consequence of enhanced absorption but also of an increased endogenous produc tion or of a decreased metabolic clearance rate.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in subclass distribution of the IgG antibodies to these three proteins may be reflecting the degree to which these proteins are entering the circulation in an antigenically viable form. OVA has been found to be resistant to proteolytic degrada tion by Kilshaw and Cant [17], Husby et al [18] and Peng et al [19], GLI and P-lac, in contrast, have been found to be largely de graded by proteolytic enzymes (as reported by Cornell [20] and Marcon-Genty et al [21]). It is therefore likely that a greater amount of OVA will enter the circulation in an antigeni cally viable form than will be seen with GLI and P-lac.…”
Section: Discussionmentioning
confidence: 88%
“…The age of the subjects was 21 (1) years [19][20][21][22] (mean (SD) [range]) and the body mass index was 21-4 (2 6) [17 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] 61 (mean (SD) [range]).…”
Section: Milk Load Studymentioning
confidence: 99%
“…ble ,3-lactoglobulin has been found to be the most resistant milk protein to enzyme hydrolysis'5 16 and is therefore absorped in greater quantities compared to other milk proteins in animal studies. '"'8 Determination of the size distribution of the absorped food proteins is important, as it is believed to be involved in the induction of immunisation or tolerance,5 and would lead to a greater understanding of the resistance of the food protein to intestinal enzymic degradation.…”
Section: Milk Load Studymentioning
confidence: 99%